2019
DOI: 10.11648/j.mcs.20190403.11
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Neuro-Fuzzy System to Determine the Blood Glucose Level of Diabetic

Abstract: Diabetes is a chronic disease that occurs when the pancreas does not produce enough insulin. The main aim of this research work was to determine the blood glucose level of diabetic patient using adaptive Neuro-fuzzy. Data of 80 diabetic patients were collected from Federal Medical Centre Jalingo. It was used for training and testing the system, Gaussian Membership function was used, hybrid training algorithm was used for training and testing, the error obtain is 0.0008333 at epoch 4 which shows that the traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…), properties of exogenous sources of glucose and insulin intake, etc. As basic mathematical representations, analytical schemes based on linear autoregressive mappings are used [8,9,10] and neural network mathematical constructions [11,12]. 2).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…), properties of exogenous sources of glucose and insulin intake, etc. As basic mathematical representations, analytical schemes based on linear autoregressive mappings are used [8,9,10] and neural network mathematical constructions [11,12]. 2).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Neural network empirical models are also generally quite efficiently tuned to specific patients and make it possible to predict future glucose levels [11,12] in his blood based on several previous values and / or some currently existing factors regulating carbohydrate metabolism. At the same time, it should be borne in mind that neural network models, before using them, require a training procedure, i.e.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At present, it is being deployed in several medical prognosis and treatment procedures. For instance, ANFIS technique is used to: determine the blood sugar levels of a diabetic person 8 predict the duration of stay in ICU at the time of cardiac arrest 9 assure security in web-based neuroscience applications; 10 predict chronic kidney disease 11 and assess the risk in software projects which find their application in healthcare scenario. 12 The empirical study undertaken in this research endeavour also found that the proposed ANFIS provides a better estimation of the security risks at early developmental phases.…”
Section: Introductionmentioning
confidence: 99%